Israel's place in the Middle East : a pluralist perspective - Rejwan, Nissim (University Press of Florida, 1998)
Annotation. To many, Jews & Arabs stand in permanent opposition, representing two clashing cultures, mentalities, & temperaments. In this book, the author maintains that this perception is historically inaccurate. From the standpoint of culture, ethnicity, & religion, he says, Israel is an integral part of the Middle East. As a nation Israel consists largely of Middle Eastern & North African Jews, native-born Israelis of European origin, & Arabs. The author shows that peaceful & neighborly relations among these groups have always prevailed & that the lot of the Jews has been better in the realm of Islam than in the West. Using Arabic, Hebrew, & English sources, the book traces the course of Arab-Jewish relations from their beginnings in pre-Islamic times to the present, & it offers a survey of Judeo-Arabic culture & literature. It also describes the ideological & cultural origins of Israel & demonstrates the way these roots shape the country's attitudes toward its surroundings.
Keywords: Jewish-Arab relations -- History.; Judaism -- Relations -- Islam.; Islam -- Relations -- Judaism.; Arab-Israeli conflict.; Israel -- Politics and government.; Israel -- Foreign relations -- Middle East.; Middle East -- Foreign relations -- Israel.; Palestine question (1948-); Relations judéo-arabes -- Histoire.; Judaïsme -- Relations -- Islam.; Islam -- Relations -- Judaïsme.; Conflit israélo-arabe.; Israël -- Politique et gouvernement.; Moyen-Orient -- Relations extérieures -- Israël.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; Arab-Israeli conflict; Diplomatic relations; Interfaith relations; Islam; Jewish-Arab relations; Judaism; Politics and government; Israel; Middle East; Joden.; Arabieren.; Culturele betrekkingen.; Buitenlandse betrekkingen.; Midden-Oosten.; Middle East.; Regions & Countries - Asia & the Middle East.; History & Archaeology.; History; Geschiedenis (vorm)